Reflection in Action: A Key to Developing Competences for the Teaching of Science - Antonio Fernández-Crispín; María Estela Ruiz Primo; Ana Cecilia Tapia Lobatón; José Praxedis Amaro Olivera; Armando Noé Rodríguez Galván (Athens Institute for Education and Research, 2016)
The aim of this research was to identify and analyse the concepts and ideas related to the nature of science, scientific concepts, and teaching and learn about science developed by a group of teachers during a training course for the teaching of sciences skills. The educational strategy was developed from a critical position on the expository models and guided discovery. Teachers assumed the role of students, reflecting on their learning and teaching and, eventually, rebuilding this learning situation with their students. In conclusion, the workshop promoted a conceptual change related to the topics and subjects addressed in the classroom: teachers' and the students'ideas related to learning about science; the evaluation of teaching; the development of creative and critical thinking; and, the development of scientific tools. Overall the teachers enjoyed the course and reoriented their approach to working in the classroom.